The Interpersonal Transaction Scales–8 (ITS-8): A Circumplex-Based, Behaviorally Anchored Instrument Based on the CLOIT-R. (June 2020) - Sadler, Pamela; Howard, Ashley P.; Lizdek, Ivana; Woody, Erik
Using the Checklist of Interpersonal Transactions–Revised (CLOIT-R; Kiesler, 2004) as a basis, a new behaviorally anchored instrument was developed with a graded-response scale, simplified item wording, substantially fewer items, and improved consistency with the interpersonal circumplex. In a community sample (Study 1), the graded response format with simplified items showed improved octant-scale reliabilities, as well as circular structure and convergent validity comparable to the CLOIT-R. Items that performed consistently across community and undergraduate samples (Study 2) were then selected to produce an inventory with half as many items as the CLOIT-R, but with good octant-scale reliabilities and excellent circular structure. Finally, in a therapy context (Study 3), the new inventory showed excellent reliability and validity for ratings of both clients and therapists. This 48-item inventory, the Interpersonal Transaction Scales–8 (ITS-8), may be used for both self- and other-ratings in everyday interactions, as well as for observer ratings of therapeutic interactions.